ISLAMIC REVIVALISM AND ENTREPRENEURSHIP - Makmun, Abu Hassan (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
An entrepreneur is commonly defined by his traits and behaviors, such as willingness to take and bear risks and ability to recognize and exploit opportunities. However, Sarasvathy contends that this is insufficient; rather, an entrepreneur should be as well defined by his logic of reasoning, more precisely the effectual reasoning. This study argues that entrepreneurial traits, behaviors, and reasoning logic apply to Islamic revivalists (mujaddid).